In Vitro Activity of Water Extracts of Olive Oil against Planktonic Cells and Biofilm Formation of Arcobacter-like Species - Švarcová, Karolína; Hofmeisterová, Leona; Švecová, Blanka; Šilha, David (My University, 2022)
Extra-virgin olive oils contain many bioactive substances that are phenolic compounds. The survival of Arcobacter-like strains in non-buffered (WEOO) and buffered (BEOO) extracts of olive oils were studied. Time kill curves of different strains were measured in the environment of olive oil extracts of different grades. The activity of the extracts was also monitored for biofilm formation using the Christensen method. In vitro results revealed that extra-virgin olive oil extracts exhibited the strongest antimicrobial effects, especially non-buffered extracts, which exhibited strain inhibition after only 5 min of exposure. The weakest inhibitory effects were observed for olive oil extracts. A decrease in biofilm formation was observed in the environment of higher WEOO concentrations, although at lower concentrations of extracts, increased biofilm formation occurred due to stress conditions. The dialdehydic forms of oleuropein derivatives, hydroxytyrosol, and tyrosol were the main compounds detected by HPLC-CoulArray. The results indicate that not all olive oils had a similar bactericidal effect, and that bioactivity primarily depended on the content of certain phenolic compounds.
In vitro aktivita vodných extraktů olivového oleje proti planktonickým buňkám a tvorbě biofilmu Arcobacter-like species
Keywords: antimicrobial effect; Arcobacter-like; biofilm formation; HPLC; olive oil extract; antimikrobiální efect; Arcobacter-like; biofilm; HPLC; olivové oleje; extrakty